Designing Augmented Reality-Based Indonesian Marine Biota Book As An Educational Media - Caroline Soen; Andreana Lingga; Muhammad Iqbal (Universitas Pendidikan Ganesha, 2024)
Indonesia has a rich diversity of marine biota, with more than 35,000 species of flora and fauna, but many are unaware of its important role in the sustainability of the ecosystem. Therefore, it is important for children to learn about marine biota from an early age in order to increase their knowledge and foster concern for the preservation of marine ecosystems. This study aims to design an augmented reality (AR)-based Indonesian marine biota book as an educational medium. With AR, it is hoped that children's interest and understanding of marine biodiversity will increase. The methods used include literature review, interviewing children illustrator and ocean conservation communities, and the development of interactive AR books and applications. This book is a mini encyclopedia about species, habitats, and conservation, complete with attractive illustrations that can be scanned through an application on the Google Play Store to activate AR animation. The work process uses digital techniques in Clip Studio Paint for illustrations, animation in Adobe After Effects, and AR with Unity.